Case reportWerner syndrome – a premature aging syndrome that can mimic scleroderma - Reich, Adam; Heisig, Monika; Baran, Eugeniusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
A 17-year-old male patient was admitted to our department with a suspected scleroderma. The first skin symptoms appeared on the upper and lower extremities as a hardening of the skin about 10 years earlier. On admission upper and lower extremities were very thin, and the skin on the extremities was hardened with prominent atrophy of subcutaneous tissue. On both lower legs multiple ulcers were present. X-ray examination of the wrists and ankles revealed decreased bone density, signs of arthropathy and soft tissue calcifications. The patient also presented scoliosis, gynecomastia and a very specific, “bird-like” appearance of the face. Laboratory investigations revealed only hyperglycaemia. Circulating antinuclear antibodies were absent. Based on clinical appearance Werner syndrome was diagnosed.